Danièle Huillet, Jean-Marie Straub "objectivists" in cinema - Turquety, Benoît 1974- (Film culture in transition, 2020)
Danièle Huillet and Jean-Marie Straub collaborated on films together from the mid-1960s through the mid-2000s, making formally radical adaptations in several languages of major works of European literature by authors including Franz Kafka, Bertolt Brecht, Friedrich Hölderlin, Pierre Corneille, Arnold Schoenberg, Cesare Pavese, and Elio Vitorrini. The impact of their work comes in part from a search for radical objectivity, a theme present in certain underground currents of modernist art and theory in the writings of Benjamin and Adorno and in a long-forgotten movement of American modernist poetry, "Objectivism," whose members included Louis Zukofsky, George Oppen, and Charles Reznikoff, with connections to William Carlos Williams and Ezra Pound. Through a detailed analysis of the films of Straub and Huillet, the works they adapted, and Objectivist poems and essays, Benoît Turquety locates common practices and explores a singular aesthetic approach where a work of art is conceived as an object, the artist an anonymous artisan, and where the force of politics and formal research attempt to reconcile with one another